2020
DOI: 10.9734/irjpac/2020/v21i1230233
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Kinetics of Carbofuran in the Soil and Its Residues in Sugarcane

Abstract: A field experiment was conducted to determine the dissipation kinetics of carbofuran and its metabolite (Carbofuran 3-OH) in the soil and their terminal residue in sugarcane. The experimental plots were subjected to application of carbofuran 3G (1.0 kg a.i./ha) at the time of planting and 60 days after planting of sugarcane variety CoN 07072 grown with recommended agronomic practices. The soil samples were periodically collected at 0 (2 hrs.), 1, 3, 5, 10, 20, 30, 60 and 90 days after last application of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The concentration of carbofuran residues in the flesh was below the detection limit at Day 0 after the application rate of 17 kg/ha (Table 3). The rapid degradation of carbofuran and its metabolites after application has been reported for other crops (Singh and Kalra, 1992;Iqbal et al, 2007, Saini et al, 2020.…”
Section: Carbofuran and Its Metabolite Residues In Watermelon Plantsmentioning
confidence: 66%
See 1 more Smart Citation
“…The concentration of carbofuran residues in the flesh was below the detection limit at Day 0 after the application rate of 17 kg/ha (Table 3). The rapid degradation of carbofuran and its metabolites after application has been reported for other crops (Singh and Kalra, 1992;Iqbal et al, 2007, Saini et al, 2020.…”
Section: Carbofuran and Its Metabolite Residues In Watermelon Plantsmentioning
confidence: 66%
“…Iqbal et al (2007) reported that a high concentration of carbofuran residue (0.039 mg/kg) was detected in brinjal after Day 3 of suspension application and became negligible after Day 7. In sugarcane, the concentration of carbofuran and carbofuran-3-hydroxy in sugarcane leaf and juice was below the quantification limit at the time of harvest (Saini et al, 2020).…”
Section: Introductionmentioning
confidence: 89%